From microRNAs to targets: pathway discovery in cell fate transitions - Subramanyam, Deepa (2011)
MicroRNAs (miRNAs) are 22 nt non-coding RNAs that regulate expression of downstream targets by messenger RNA (mRNA) destabilization and translational inhibition. A large number of eukaryotic mRNAs are targeted by miRNAs, with many individual mRNAs being targeted by multiple miRNAs. Further, a single miRNA can target hundreds of mRNAs, making these small RNAs powerful regulators of cell fate decisions. Such regulation by miRNAs has been observed in the maintenance of the embryonic stem cell (ESC) cell cycle and during ESC differentiation. MiRNAs can also promote the dedifferentiation of somatic cells to induced pluripotent stem cells. During this process they target multiple downstream genes, which represent important nodes of key cellular processes. Here, we review these findings and discuss how miRNAs may be used as tools to discover novel pathways that are involved in cell fate transitions using dedifferentiation of somatic stem cells to induced pluripotent stem cells as a case study.